Determinação de halogênios em carvão, coque petroquímico e alimentos após combustão iniciada por microondas - Mesko, Márcia Foster (2008)
The microwave-induced combustion (MIC) method was applied for coal and petroleum coke digestion for further determination of bromine, chlorine, fluorine and iodine by ion chromatography (IC). Samples (up to 500 mg) were combusted at 20 bar of oxygen and analytes were absorbed either in water or (NH4)2CO3 (10 to 50 mmol l-1) solutions. A reflux step was applied to improve analyte absorption. Accuracy was evaluated for Br, Cl, F and I using coal and coke certified reference materials as well as using spike recoveries. For Br, Cl and F the agreement was from 96 to 103% using 50 mmol l-1 (NH4)2CO3 as absorbing solution and reflux step. For I, recoveries were higher than 97%. Bromine, Cl and I were also determined in MIC digests by inductively coupled plasma mass spectrometry (ICP-MS), inductively coupled plasma optical emission spectrometry (ICP OES), and F by ion selective electrode (ISE) with agreement higher than 95% to the values obtained using IC. The procedure was also compared with wet digestion procedure for coal and petroleum coke, as well as with procedures of extraction using different solutions. Neverthless, the results were always lower than those obtained using MIC. Temperature during combustion was higher than 1350 and 1500 ºC for coal and petroleum coke, respectively, and the residual carbon content was lower than 1%. Using MIC technique up to eight samples may be simultaneously processed and a single absorbing solution may be suitable for all analytes and determination techniques. The limits of detection (LODs, 3s) using the proposed MIC-IC method were 2.5, 0.8, 0.25 e 3.0 mg g-1, respectively. Additionally, the same MIC procedure was applied for food sample digestion for further iodine determination by ICP-MS. Using MIC technique the LOD for iodine by ICP-MS was 0.001 mg g-1 and the agreement with certified values for iodine in food were higher than 96% for all analyzed samples.